2003
DOI: 10.1046/j.1365-2958.2003.03350.x
|View full text |Cite
|
Sign up to set email alerts
|

Proinflammatory signalling stimulated by the type III translocation factor YopB is counteracted by multiple effectors in epithelial cells infected with Yersinia pseudotuberculosis

Abstract: Summary

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
74
0
1

Year Published

2005
2005
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 72 publications
(82 citation statements)
references
References 53 publications
2
74
0
1
Order By: Relevance
“…It is, therefore, possible that the differences seen above are due to YopB and not YopJ, as YopB can also affect eukaryotic signal transduction [36]. To assess this, we examined the effects of Y. pestis KIM5-3001.48 (YopB + YopJ -), a injection competent poly-yop deletion mutant either carrying (YopB + YopJ + ) or not carrying (YopB + YopJ -) the pYopJ-GSK plasmid.…”
Section: Effect Of Injection Competent Vs Incompetent Strains Of Y mentioning
confidence: 99%
“…It is, therefore, possible that the differences seen above are due to YopB and not YopJ, as YopB can also affect eukaryotic signal transduction [36]. To assess this, we examined the effects of Y. pestis KIM5-3001.48 (YopB + YopJ -), a injection competent poly-yop deletion mutant either carrying (YopB + YopJ + ) or not carrying (YopB + YopJ -) the pYopJ-GSK plasmid.…”
Section: Effect Of Injection Competent Vs Incompetent Strains Of Y mentioning
confidence: 99%
“…to activate NF-B, which subsequently gives rise to a proinflammatory host cell response, including production of, e.g., IL-8 (17,39,(45)(46)(47). NF-B is a key transcription factor involved in innate immune responses to pathogens (9).…”
Section: Resultsmentioning
confidence: 99%
“…The repressive mechanisms responsible depend on bacterial injection of host cells with type III secretion effectors. For example, the Y. pestis secreted effector YopJ is a potent inhibitor of the NF-kB and MAPK signalling pathways (Sweet et al, 2007), and YopE has been shown to strongly inhibit activation of JNK, ERK and NF-kB with a coincident suppression of interleukin (IL)-8 production (Viboud & Bliska, 2005;Viboud et al, 2003). The Yersinia V-antigen has been reported to induce IL-10, which represses innate immunity (Brubaker, 2003;Overheim et al, 2005;Philipovskiy et al, 2005) but this activity has been challenged in more recent reports (Pouliot et al, 2007).…”
Section: Introductionmentioning
confidence: 99%